Evaluation of Herbicide Combination Against Mixed Weed Flora in Direct Seeded Rice (Oryza sativa L.) - Verma, Saurabh; Verma, D. K.; Giri, S. P.; Pandey, Alok; Singh, D. P. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted to study the effect of pre and post emergence herbicide combination practices on complex weed flora in direct seeded rice (Oryza sativa) during kharif 2007 and 2008. The treatments consisted of Bispyribac-sodium (10 SC) @ 25 g ai ha-1 at 20 DAS, Pendimethlain (38.7 CS) @ 1000 g ai ha-1 as pre em fb Bispyribac, Oxadiargyl (80 WP) @ 100 g ai ha-1 as pre em fb Bispyribac-sodium, Pendimethlain (38.7 CS) as pre em fb Bispyribac fb manual weeding at 45 DAS, Pendimethlain (38.7 CS) as pre em fb manual weeding at 30 DAS, Bispyribac sodium (10 SC) @ 25 g ai ha-1+Chlorimuron methyl+Metsulfuron methyl (20 WP) @ 4.0 g ai ha-1 at 20 DAS in comparison to passing cono weeder and hand weeding at 20 and 40 DAS and weedy check condition in RBD with three replications. The results indicated that the density and dry weight of weeds were significantly lower with two hand weeding, application with cono weeder and the among herbicide combinations Pendimethalin fb Bispyribac fb hand weeding treatments. Higher WCE and grain yields of direct seeded rice were significantly higher with application of above mentioned herbicide combinations and were at par with hand weeding and cono weeder treatments. The comparative economic study reveals that the herbicide combination treatments, Pendimethalin fb Bispyribac fb hand weeding recorded highest net return of ` 18,791/- with B:C ratio of 1.97 followed by Pendimethalin fb Bispyribac which recorded net return of ` 18,500/- with slightly higher B:C ratio of 2.03.